Analysis of sago starch (Metroxylon sagu) quality from various cultivars in the Yapen Islands, Papua, Indonesia - SOETJIPTO MOELJONO; ENDRA GUNAWAN; SUSILO BUDI HUSODO; JULIUS D. NUGROHO; WOLFRAM Y. MOFU; ANA TAMPANG; MATHEUS BELJAI; B. M. G. SADSOEITOEBOEN; FRANCINA F. KESAULIJA; MAHMUD MAHMUD; MARTHINUS P. IWANGGIN; VIKTOR I. SIMBIAK; SUSANTI TASIK; MELISA S. WORABAI; DINA ARUNG PADANG; RADITE YOGASWARA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Moeljono S, Gunawan E, Husodo SB, Nugroho JD, Mofu WY, Tampang A, Beljai M, Sadsoeitoeboen BMG, Kesaulija FF, Mahmud, Iwanggin MP, Simbiak VI, Tasik S, Worabai MS, Padang DA, Yogaswara R. 2025. Analysis of sago starch (Metroxylon sagu) quality from various cultivars in the Yapen Islands, Papua, Indonesia. Biodiversitas 26: 2717-2725. Sago (Metroxylon sagu) is a palm plant that produces carbohydrates and possesses significant potential to support food security and industry in the Yapen Islands District, Papua. This study aimed to analyze the quality of sago starch from the various cultivars that thrive in the region. A quantitative method using a survey research design was applied, with sampling conducted in the Eastern and Western Yapen Sub-Clusters from January to March 2024. The physicochemical analysis of sago starch was carried out at the Forest Products Technology Laboratory of the University of Papua. The results indicate a diversity of sago cultivars in both areas, with the Woru and Noyn cultivars dominating Western Yapen, and Kurai and Amiri in Eastern Yapen. The starch yield varied significantly between cultivars, with the Noyn (630 kg/tree) and Huworu (264 kg/tree) cultivars recording the highest production. The physicochemical characteristics revealed a variation in moisture content (1.66-4.78%), fineness (88.98-95.12%), ash content (0.91-1.39%), and degree of acidity (1.3-5.7). The Kurai, Huworu, and Woru cultivars exhibited superior characteristics for food industry applications, while Makubong and Dami showed potential for non-food applications. The development of sago agro-business in the Yapen Islands District necessitates the selection of appropriate cultivars and the strengthening of post-harvest management systems to optimize both economic and ecological value.